2020
DOI: 10.2196/21597
|View full text |Cite
|
Sign up to set email alerts
|

Collective Response to Media Coverage of the COVID-19 Pandemic on Reddit and Wikipedia: Mixed-Methods Analysis

Abstract: Background The exposure and consumption of information during epidemic outbreaks may alter people’s risk perception and trigger behavioral changes, which can ultimately affect the evolution of the disease. It is thus of utmost importance to map the dissemination of information by mainstream media outlets and the public response to this information. However, our understanding of this exposure-response dynamic during the COVID-19 pandemic is still limited. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
140
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(153 citation statements)
references
References 80 publications
7
140
0
6
Order By: Relevance
“…The third, the country of study and the references. Category Proxy data type Country and reference Adoption of NPI Mobile phones and/or vehicles through location intelligence and measurement platforms USA [367] , [368] , [369] , [370] , [371] , [372] Twitter Twitter population [373] , [374] Wikipedia and Reddit Canada, Italy, USA, UK [375] Google USA [376] ; 130 countries [377] TV USA [378] Mobility changes Mobile phones and/or vehicles through location intelligence and measurement platforms USA [37] , [38] , [379] , [380] Facebook Italy [39] Citymapper app 22 countries [381] …”
Section: Measuring Npis Via Proxy Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The third, the country of study and the references. Category Proxy data type Country and reference Adoption of NPI Mobile phones and/or vehicles through location intelligence and measurement platforms USA [367] , [368] , [369] , [370] , [371] , [372] Twitter Twitter population [373] , [374] Wikipedia and Reddit Canada, Italy, USA, UK [375] Google USA [376] ; 130 countries [377] TV USA [378] Mobility changes Mobile phones and/or vehicles through location intelligence and measurement platforms USA [37] , [38] , [379] , [380] Facebook Italy [39] Citymapper app 22 countries [381] …”
Section: Measuring Npis Via Proxy Datamentioning
confidence: 99%
“…Here, we find articles aimed at quantifying the adoption of NPIs via proxy data such as mobile phones collected by location intelligence companies [367] , [368] , [369] , [370] , [371] , [372] , Twitter [373] , [374] , COVID-19 ad-hoc apps [196] , Wikipedia and Reddit [375] , Google [376] , [377] , and TV viewings [378] .…”
Section: Measuring Npis Via Proxy Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This messaging may influence public perception of psychiatric and justice-involved populations and can have serious implications in the development of policies regarding public safety. A recent study found that public attention online was more likely to be driven by media coverage than data regarding the incidence rate of COVID-19 ( Gozzi et al, 2020 ). As emerging evidence indicates the influence of media coverage, it is crucial to evaluate how stigmatization of mental illness and justice-involved individuals may present within the media during COVID-19.…”
Section: Stigmatization and Covid-19mentioning
confidence: 99%
“…El cumplimiento de estas medidas está asociado a la percepción individual de riesgo y vulnerabilidad. Además, la información emitida por los medios de comunicación es capaz de dirigir el interés y el comportamiento de la población, por lo que es necesario que se difunda información veraz que fomente el cumplimiento de las medidas sanitarias 29 . Recientemente, se ha demostrado cómo las declaraciones de personajes famosos sobre tratamientos inapropiados para la COVID-19 produce un aumento significativo de la demanda de estos productos a pesar de la ausencia de demostración de su eficacia y, en algunos casos, incluso de su demostrado perjuicio 30 .…”
Section: Redes Sociales Y Medios De Comunicación En Tiempos De Pandemunclassified